Bibliometric Insights into Halal Retail: Mapping of Research Trends - Prita Nurkhalisa Maradjabessy; Roaida Yanti; Qurtubi; Danang Setiawan; Harlina Suzana Jaafar (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2024)
This study systematically examines and assesses the existing literature on halal retail to identify trends and emerging areas of interest. It seeks to offer insightful advice for market strategies, policy development, and research opportunities in the ever-changing halal retail sector. The study uses a bibliometric analysis and research mapping approach, employing data from 994 articles sourced from Google Scholar (GS). The data was analyzed using Harzing's Publish or Perish (PoP) to identify current and promising research areas. The study highlights the importance of exploring these trends further and combining them with less explored research areas. The relatively limited research in halal retail over the past decade is also noted, presenting a timely opportunity for deeper investigation. Originality lies in its comprehensive bibliometric analysis of the halal retail sector over a decade. It provides a unique perspective on evolving trends and emerging research areas, offering a valuable resource for scholars, market strategists, and policymakers interested in the halal market. Practical implications are significant for market strategists and policymakers in the halal retail sector. By identifying current trends and gaps, the study provides insights that can inform strategic decisions, enhance market positioning, and drive policy development to support the growth of halal retail.